Spontaneous pulmonary adenocarcinoma in a common marmoset (Callithrix jacchus). Issue 6 (26th August 2021) - Mineshige, Takayuki; Inoue, Takashi; Kawai, Kenji; Seki, Fumiko; Yurimoto, Terumi; Hata, Jun‐ichi; Watanabe, Kenichi; Kobayashi, Yoshiyasu; Sasaki, Erika
Abstract: A seven‐year‐old female common marmoset ( Callithrix jacchus ) presented with weight loss. Imaging revealed a left thoracic mass, confirmed at necropsy. Histology and immunohistochemistry suggested a well‐differentiated pulmonary adenocarcinoma. No evidence of local lymphovascular invasion or distant metastasis was observed. This is the first report of pulmonary adenocarcinoma in marmosets.